2004
DOI: 10.1111/j.1365-2265.2004.02192.x
|View full text |Cite
|
Sign up to set email alerts
|

Different responses to chronic somatostatin analogues in patients with central hyperthyroidism

Abstract: Chronic administration of long-acting somatostatin analogues in patients with central hyperthyroidism caused a marked decrease of FT3 and FT4 levels in all patients but one with TSH-oma, while patients with PRTH did not respond at all. Thus, administration of long acting somatostatin analogues for at least 2 months can be useful in the differential diagnosis in problematic cases of central hyperthyroidism. Furthermore, the present findings exclude the possibility of a beneficial effect of chronic administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 40 publications
(82 reference statements)
1
35
0
5
Order By: Relevance
“…every 28 days for 2-4 months, sampling at 0 and every 28 days just before the new injection) in patients with central hyperthyroidism caused a marked decrease of free T4 and free T3 levels in all but one patient with TSHoma, while patients with RTH did not respond at all [34]. Thus, administration of long-acting somatostatin analogs for at least 2 months can be useful in the differential diagnosis in problematic cases of central hyperthyroidism.…”
Section: Recommendationsmentioning
confidence: 99%
“…every 28 days for 2-4 months, sampling at 0 and every 28 days just before the new injection) in patients with central hyperthyroidism caused a marked decrease of free T4 and free T3 levels in all but one patient with TSHoma, while patients with RTH did not respond at all [34]. Thus, administration of long-acting somatostatin analogs for at least 2 months can be useful in the differential diagnosis in problematic cases of central hyperthyroidism.…”
Section: Recommendationsmentioning
confidence: 99%
“…In a recent study (21), administration of octreotide-LAR over two months showed significant reduction or normalization of free thyroid hormones in seven of eight patients with TSH-oma, while none of the patients with pituitary RTH responded to this therapy. In one patient of our series, therapy with a somatostatin analog resulted in shrinkage of the tumor as known to occur under octreotide in 50% of the patients (22).…”
Section: Discussionmentioning
confidence: 92%
“…Длительное назначение аналогов соматоста-тина пролонгированного действия (20-30 мг внутри-венно каждые 28 дней в течение 2-4 мес; контроль-ные анализы крови исходно и каждые 28 дней непо-средственно перед новой инъекцией) сопровожда-лось снижением уровней св.Т 3 и св.Т 4 практически у всех пациентов с ТТГ-омами и было неэффектив-ным у пациентов с РТГ [28]. Следовательно, назначе-ние аналогов соматостатина пролонгированного действия по меньшей мере в течение 2 мес может использоваться для дифференциальной диагностики сомнительных случаев центрального гипертиреоза.…”
Section: доказательность слабая слабая рекомендацияunclassified
“…Следовательно, назначе-ние аналогов соматостатина пролонгированного действия по меньшей мере в течение 2 мес может использоваться для дифференциальной диагностики сомнительных случаев центрального гипертиреоза. Длительное назначение аналогов соматостатина па-циентам с РТГ, по имеющимся данным, не имело никаких клинических преимуществ [28].…”
Section: доказательность слабая слабая рекомендацияunclassified